THE REALITY OF THE PLACE WHERE WE LIVE: Interview with John Davies. (4th May 2019) - Smith, Olga
Abstract : This interview with British photographer John Davies traces the development of the artist's career from the 1970s to the present day, with a particular focus on his engagement with the subject of landscape representation in the urban context. The interview highlights a number of key aspects of Davies' practice, including the use of the high vantage point and geographical maps, and discusses the social and cultural implications of designating landscape as a product of historical process.